Electronic system for Static Postural Re-education in Real Time - Estévez Pedraza, A G; Martínez Méndez, R; Rodríguez Arce, J; Portillo Rodríguez, O (Revista Mexicana de Ingenieria Biomedica, 2017)
This paper presents an electronic system aimed to assist on the postural evaluation by measuring the weight distribution on the feet. Postural evaluation is commonly used by physiotherapists in order to correct muscle-skeletal problems such as those derived from ageing, accidents, diseases, etc. The developed electronic system was validated preliminary using video cameras to confirm the correct postures of the subject under test. With the obtained data it is possible to corroborate that the proposed system is capable to assist on the correction of the postural position in real time. The main limitation of this work is the reduced number of tests, due to this only preliminary results are presented. The main novelty of this work is the proposed solution to evaluate and help to correct the posture by using a portable electronic device based on force sensors. Derived from the presented results it can be concluded that the proposed system is capable to assist on the evaluation and correction of postural position in real time.